Management of Tietze Syndrome: Acupuncture and Cupping as an Effective Treatment Approach: A Case Study - Satyal, Jaya; Shrestha, Rakesh; K.C., Pradeep; Khatiwada , Kashi; Rouniyar, Nabina; Chandra , Avinash (Annapurna Journal of Health Sciences, 2023)
Tietze syndrome is a rare inflammatory disorder characterized by chest pain at costochondral junction with an idiopathic etiology. A patient came to the Central Ayurved Hospital Nardevi with an excruciating pain since 5 months. Patient stated that the several medications were tried without any success. Patient was further assessed via radiologically and laboratory. Results were within normal limits. Hence, patient was given 12 sessions of acupuncture along with cupping as the means for pain management. Patient was initially assessed via VAS (Visual Analogue Scale) before the commencement of the treatment session. This case demonstrates that the acupuncture can be an effective treatment approach for the management of Tietze syndrome.